Updates on the Einstein Probe mission - Yuan, Weimin; Zhang, Chen; Ling, Zhixing; Zhang, Yonghe; Cai, Zhiming; Liu, Huaqiu; Sun, Shengli; Sun, Xiaojin; Chen, Yong; Cui, Weiwei; Han, Dawei; Jia, Shumei; et al. (SPIE, 2024)
The Einstein Probe (EP), launched successfully on January 9, 2024, is a space mission dedicated to X-ray time-domain astrophysics with a broad range of scientific goals. EP carries a wide-field X-ray telescope to monitor the soft X-ray sky in 0.5–4 keV with a 3600 square-degree field-of-view and a narrow-field X-ray telescope for follow-up observations in 0.3–10 keV and precise source locating. The satellite is currently in the commissioning phase, undertaking in-orbit tests and calibration of the spacecraft and payloads, and tests for the data telemetry and space-ground communication. The test and calibration results achieved so far show that the spacecraft and instruments are working normally, and all the performances meet the requirements of the project design. EP is expected to start normal science operations from late June or early July, 2024.